Student Teachersâ Teaching Skill Development Through Mentoring Process - Rozak, Diana Rahmawati (Perspective Jurnal Pendidikan Bahasa Inggris, 2014)
Abstract This study is about student teachersâ basic teaching skills especially in delivering gaining attention, presenting stimulus materials, and assessing performance. The purposes of this study is to find out whether or not student teachersâ skill in gaining attention, presenting stimulus materials, and assessing performance. Was developed during their teaching practice period. To achieve the first purpose, the data were collected through observations and interviews. The obervation was conducted during student teachersâ teaching-learning sessions. The interviews was conducted to support the data from interview. The source for interview was student teachersâ mentor teachers. The result of this study was that two of four student teachers had developed their teaching skills in gaining attention while the other two did not develop their skills. This study has showed that besides studentsâ ability, willingness and support from mentor teachers and peers are needed to develop their teaching skills Key words: basic teaching skills, student teacher, teaching practice, gaining attention, presenting stimulus materials, and assessing performance.